2016
DOI: 10.1007/s13244-016-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

Post traumatic deafness: a pictorial review of CT and MRI findings

Abstract: Hearing loss is a common functional disorder after trauma, and radiologists should be aware of the ossicular, labyrinthine or brain lesions that may be responsible. After a trauma, use of a systematic approach to explore the main functional components of auditory pathways is essential. Conductive hearing loss is caused by the disruption of the conductive chain, which may be due to ossicular luxation or fracture. This pictorial review firstly describes the normal 2-D and 3-D anatomy of the ossicular chain, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…This is plausible because dislocation of the incus, which is embedded between the malleus and stapes, should affect both joints. Another plausible explanation for the lower prevalence of the often subtle incudostapedial dislocation in our CT-based study might be the initial hemotympanum, which makes an accurate radiologic assessment difficult, especially in early trauma diagnostics and for slight dislocations [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is plausible because dislocation of the incus, which is embedded between the malleus and stapes, should affect both joints. Another plausible explanation for the lower prevalence of the often subtle incudostapedial dislocation in our CT-based study might be the initial hemotympanum, which makes an accurate radiologic assessment difficult, especially in early trauma diagnostics and for slight dislocations [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In early development of CT, cochlear partitioning and soft tissue membranes were not adequately visualized (10) (11). Recent advances in MDCT, including the development of scanners with 32 detector rows (64 effective sections) for depiction of normal anatomy and pathologic states in the temporal bone, allow the acquisition of isotropic voxels that can be reconstructed and used in the multiplanar reconstructions of volumetric CT images (12). This technique gives radiologists the opportunity to visualize the anatomic structures of the middle and inner ears accurately (table 1) (13).…”
Section: Ctmentioning
confidence: 99%
“…(6) (54) visualization of the cochlear partitioning (9). A recent paper by Maillot et al (12) indicated that MDCT allows radiologists to examine the complex anatomy of the temporal bone with sub-millimeter resolution and is the first modality of choice. Indeed, it is capable of revealing a broad spectrum of ossicular lesions that may not be apparent on the basis of clinical findings alone.…”
Section: Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…SFOF-VR can accurately locate the lesion and clearly show their relations, and thus provides more anatomic information for selecting optimal surgical path or treatment method. Furthermore, the combination of the technology and finite element modeling will have great effect on the study of regional anatomy, biomechanical analysis and surgical design [9,10].…”
Section: Figure 1 Sfof-vr 3dmentioning
confidence: 99%